2009 International Conference on Information Management and Engineering 2009
DOI: 10.1109/icime.2009.66
|View full text |Cite
|
Sign up to set email alerts
|

To Investigate the Success and Failure Factors of ERP Implementation within Malaysian Small and Medium Enterprises

Abstract: in recent years ERP, as a comprehensive new system, has been used by many Malaysian companies. It has been successful in some and in some others it has failed. This article assesses 15 success factors and 8 failure factors in SME companies and tries to recognize the effective ones. The results show that the two most important failure factors in implementing ERP in Malaysian SMEs are 'poor planning or poor management ' and 'inappropriate training methods' and the most important success factors are ' Implementin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 8 publications
1
24
0
Order By: Relevance
“…The study conducted by Elmam and Koru [3] indicates that the top 5 causes of project failure are non-technical issues. These results support the claims that are made by researchers such as Noudoostbeni, Yasin and Jenatabadi [18].…”
Section: B Causes Of Software Project Failuresupporting
confidence: 82%
See 1 more Smart Citation
“…The study conducted by Elmam and Koru [3] indicates that the top 5 causes of project failure are non-technical issues. These results support the claims that are made by researchers such as Noudoostbeni, Yasin and Jenatabadi [18].…”
Section: B Causes Of Software Project Failuresupporting
confidence: 82%
“…Noudoostbeni et al [18] indicated that 67% of SDPs resulted in failure because of soft skills or soft issues. Although it is indicated that soft issues are one of the major sources of failure of SDPs, limited research work has being conducted regarding the role of soft skills within SDPs.…”
Section: B Causes Of Software Project Failurementioning
confidence: 99%
“…SMEs, small in its working capital, assets and skilled workforce etc, are affected in larger degree, especially those which are involved with supplying products and trading or services to other businesses. The most important key success factor in Malaysian SMEs is "team work" (Noudoostbeni et al, 2009). Also, according to Sim (1991), Sim and Yap (1997) and hashim (2000), limited attention is given to research in the field of strategic planning, and also researchers investigating SMEs has given limited attention to strategic planning in SMEs in Malaysian context (Hin et al, 2013).…”
Section: Business and Management Horizonsmentioning
confidence: 99%
“…His findings show that lecturer and on the job training and computer based training are among the most used training methods in Malaysian SMEs. Figure 3 training methods of ERP in SME sectors in Malaysia (Noudoostbeni et al, 2009b) In another study done by Mozaffar, she refers to the findings from Gartner and other sources that indicate the importance of the training in ERP implementation (Mozaffar & Mozaffar, 2009). Then by introducing the impact of business process and its role in new techniques like 6sigma, Lean manufacturing, JIT, she argues that new enterprise systems (i.e.…”
Section: Product Independent Erp Training Modelmentioning
confidence: 99%
“…In Malaysia, a research study was done to investigate the different training methods of ERP in SME sectors in Malaysia (Noudoostbeni et al, 2009b). Table 2 shows the summary of training methods identified by him.…”
Section: Product Independent Erp Training Modelmentioning
confidence: 99%